STRATEGIES FOR MITIGATING RESISTANCE TO ENGLISH ACQUISITION IN TECHNOLOGY-ENHANCED EDUCATIONAL SETTINGS - Bukhari, Mahin; Patoliya , Virali (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This conceptual paper delves into the complexities of surmounting resistance to English acquisition in technology-driven classrooms, with a focus on psychological, sociocultural, and technological impediments. The reluctance often originates from the perception of English as inconsequential to technical education, compounded by cultural barriers, lack of motivation, and technological constraints. Drawing upon insights from extant literature, the paper scrutinizes the pivotal role of educators, the potential of nascent technologies, and the significance of harmonizing pedagogical approaches with students' vocational aspirations. It also underscores the critical nature of teacher preparedness, continuous professional growth, and the cultivation of nurturing learning environments. The discourse on the future of English acquisition in technology-centric classrooms underscores the imperatives of innovation, inclusive, and the assimilation of cutting-edge tools like artificial intelligence and virtual reality. Mitigating systemic and individual obstacles will be imperative in augmenting engagement and ensuring that English acquisition evolves into an indispensable and pertinent facet of technical education.